Pattern of Children Presenting with Inguinal Hernia and Hydrocele- Experience in a Tertiary Level Hospital (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Inguinal hernias and hydroceles are among the common surgical problems in children. Both the hernia and hydrocele share a similar aetiology. Inguinal hernia in a child is usually an indirect inguinal hernia due to patent processus vaginalis. Likewise a fluid filled sac typically found in the scrotum may result from patent processus vaginalis or due to an imbalance between the secretion and absorption within the tunica vaginalis. Very little study was done in Bangladesh on inguinal hernia and hydrocele though these are very common in children.Objective: To observe the pattern of inguinal hernia and hydrocele amongst the children reported to a tertiary level hospital.Materials and Methods: This observational study was carried out in the Department of Paediatric Surgery, Combined Military Hospital, Dhaka during the period of January 2014 to December 2017. During the study period, a total of 258 children with inguinal hernia and hydrocele admitted in this hospital for operative treatment were included in this study.Results: During the study period 258 children with inguinal hernia and hydrocele were operated. Among them 246 (95.35%) had inguinal hernia and 12(4.65%) had hydrocele. Out of the children with inguinal hernia 206 (83.74%) were male and 40(16.26%) were female with male female ratio of 5.15:1. All had indirect inguinal hernia. Right side was involved in 140(56.91%) children. Out of 246 children with inguinal hernia, 161(65.44%) reported between 6 months to 5 years. Thirteen (5.28%) presented before 6 months and 72 (29.27%) presented after 5 years of age. All children were operated by traditional open method as admitted case. Among 12 children with hydrocele 10(83.33%) had right sided hydrocele and 2(16.67%) had hydrocele on the left side.Conclusion: Inguinal hernia and hydrocele occur most frequently in premature neonates. Inguinal hernia does not resolve spontaneously and there is high risk of incarceration requiring operative treatment as early as possible.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 46-50